2012
DOI: 10.1111/jocn.12009
|View full text |Cite|
|
Sign up to set email alerts
|

Risk factors for surgical site infection in breast surgery

Abstract: In breast surgery careful assessment, documentation and adherence to aseptic practices are important with all patients. Patients with heavy weight need special attention. The need for antimicrobial prophylaxis in re-operations and the need of surgical drains in lumpectomies are important to consider carefully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…11 Teija-Kaisa et al found that reoperation was an independent risk factor for SSI after BCS, however the type of previous operation was not described. 12 Using data from the National Surgical Quality Improvement Program, de Blacam reported that wound complications (SSI or wound disruption) after BCS were nearly twice as likely when there was a prior (unspecified) operation within 30 days. 19 …”
Section: Discussionmentioning
confidence: 99%
“…11 Teija-Kaisa et al found that reoperation was an independent risk factor for SSI after BCS, however the type of previous operation was not described. 12 Using data from the National Surgical Quality Improvement Program, de Blacam reported that wound complications (SSI or wound disruption) after BCS were nearly twice as likely when there was a prior (unspecified) operation within 30 days. 19 …”
Section: Discussionmentioning
confidence: 99%
“…In addition to contaminated or dirty site of wound, high body mass index, re-operation and use of post-surgical drain increased the infection risk of surgical site infection among lumpectomies and mastectomies patients [9].…”
Section: Introductionmentioning
confidence: 99%
“…In agreement, the present study showed that the use of drain in thyroid surgery increased the risk of SSI. The use of drains in other areas with low risk of post-operative infection, such as breast surgery, has also been associated with a higher risk of SSI [ 21 ]. Therefore, the use of drain in routine thyroid surgery should be discouraged.…”
Section: Discussionmentioning
confidence: 99%